(untitled) (Praxis Educativa, 2014)
The theory known as Rapport au Savoir (AKR) or Action Knowledge Relation appears as an answer to the classic theories about success or failure at school. This theory is born at the Research Laboratory ESCOL (in Spanish: school knowledge and local communities), attached to the Science of Education Department at Paris University (France). The AKR has a socio-anthropological approach and proposes the figures of learning, important dimensions to understand the sense that the activity-action related to knowledge has for a singular person. This article describes the results of a research performed at some schools in the municipalities of Cali, Candelaria and Vereda el Cabuya (Department of Valle del Cauca).